A degradable adhesive

By using starch-based materials and other components in the adhesive layer of the adhesive layer, and setting a degradation layer between the surface layer and the adhesive layer, storing substances that can accelerate degradation, the existing degradation problem of constant degradation effect is solved, and efficient control of the degradation rate and environmentally friendly degradation effect are achieved.

CN116179105BActive Publication Date: 2025-03-28KUNMING HEYU STICKINESS PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310200861.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-03-28
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The degradation effect of existing degradable self-adhesive adhesives is constant, resulting in short service life or excessive degradation time, causing environmental pollution.

Method used

A starch-based material is used as an adhesive layer, accompanied by polycaprolactone, ZnO, diisopropyl peroxide and other components, and a degradation layer is set between the surface layer and the adhesive layer to store substances that can accelerate degradation, and the degradation rate of the self-adhesive adhesive is adjusted by controlling the release of substances in the degradation layer.

Benefits of technology

It has achieved efficient control of the degradation rate of self-adhesive adhesives, with the disintegration rate reaching more than 90% within 180 days, and accelerated degradation through internal degradation solution to reduce environmental pollution, and has commercial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116179105B_ABST
    Figure CN116179105B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of self-adhesive stickers, and specifically relates to a degradable self-adhesive sticker. The specific technical scheme is: a degradable self-adhesive sticker, the self-adhesive sticker includes a surface layer, an adhesive layer and a bottom layer, the adhesive layer is a starch-based material, and the formula includes, by weight: 10 to 30 parts of starch, 10 to 20 parts of polycaprolactone, 0.5 to 10 parts of alkali, 0.3 to 1 part of ZnO, 0.3 to 1 part of diisopropylbenzene peroxide, and 50 to 150 parts of water. The present invention provides a new self-adhesive sticker, and the degradation rate of the adhesive layer material is high, and the disintegration rate reaches more than 90% within 180 days under composting conditions. The present invention also provides a self-adhesive sticker with a controllable degree of degradation. When the self-adhesive sticker needs to be torn off, the degradation liquid inside the self-adhesive sticker can be manually released to help the self-adhesive sticker disintegrate and degrade from the inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of self-adhesive stickers, and in particular relates to a degradable self-adhesive sticker. Background Art

[0002] Self-adhesive stickers are an important product that is indispensable to modern life and production, and are widely used in all walks of life. However, with the promotion of self-adhesive stickers, the environmental pollution problem caused by them is becoming increasingly serious.

[0003] In the prior art, there are already a large number of degradable materials, and many of these materials can also be used in the production of self-adhesive stickers. Although there are some degradable self-adhesive products, no matter which degradable material is used to prepare the self-adhesive, there is a problem: the degradation effect of the self-adhesive is constant when it is in use and discarded. This leads to a contradiction: if a very easy-to-degrade material is used, the service life of the self-adhesive is short, and the user needs to replace it frequently, which increases the cost of use. If a relatively non-degradable material is used, although it is biodegradable, it takes a very long time to degrade and will still cause environmental pollution.

[0004] Therefore, if a self-adhesive sticker whose degree of degradation changes with the use status can be provided, it will have important application prospects and environmental value. Summary of the invention

[0005] The purpose of the invention is to provide a degradable adhesive label.

[0006] To achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: a degradable self-adhesive sticker, the self-adhesive sticker comprises a surface layer, an adhesive layer and a bottom layer, the adhesive layer is a starch-based material, and the formula comprises, by weight: 10 to 30 parts of starch, 10 to 20 parts of polycaprolactone, 0.5 to 10 parts of alkali, 0.3 to 1 part of ZnO, 0.3 to 1 part of diisopropyl peroxide, and 50 to 150 parts of water.

[0007] Preferably, the base is any one of NaOH and Ca(OH)2.

[0008] Preferably, the adhesive layer formula is as follows, by weight: 15 parts of starch, 80 parts of water, 1 part of NaOH, 10 parts of polycaprolactone, 0.5 parts of ZnO and 0.5 parts of diisopropylbenzene peroxide.

[0009] Preferably, a degradation layer is provided between the surface layer and the adhesive layer; and a substance capable of accelerating the degradation of the surface layer and the adhesive layer is stored in the degradation layer.

[0010] Preferably, the release time of the substance stored in the degradation layer is controllable.

[0011] Preferably, the degradation layer comprises a storage bin, wherein dry powder material is stored in the storage bin, and the dry powder material can accelerate the degradation of the surface layer and the adhesive layer when in a liquid state;

[0012] The storage bin is placed between the surface layer and the adhesive layer, close to the storage channel, and the storage channel contains a dissolving liquid that can dissolve the powder material in the storage bin; the storage bin can be connected to the storage channel when it is necessary to accelerate the degradation of the adhesive.

[0013] Preferably, a sharp opening groove is provided at one end of the storage bin, and the opening groove is connected to the interior of the storage bin; the sharp end of the opening groove is located inside the storage channel;

[0014] The storage channel is divided into two independent spaces where liquids do not flow into each other by a separation membrane. One of the spaces accommodates the open groove, and there is a certain distance between the open groove and the separation membrane; the other space stores the dissolved liquid.

[0015] Accordingly, the method for preparing the degradable adhesive comprises the following steps:

[0016] (1) Weigh starch by weight and add it to water, stirring while adding. After fully mixing, slowly add NaOH while keeping stirring. After adding and fully mixing, keep stirring and add PCL. After adding and fully mixing, keep stirring and add ZnO and DCP. After all materials are added, continue to stir until all components are fully mixed and present a uniform flowing liquid state, and naturally cool to room temperature to obtain an adhesive material.

[0017] (2) cutting the surface layer material and the bottom layer material into required sizes and shapes to obtain the surface layer and the bottom layer respectively;

[0018] (3) applying an adhesive material onto the surface layer and forming an adhesive layer after drying;

[0019] (4) Lay the bottom layer on the side of the adhesive layer that is not in contact with the surface layer to obtain the desired self-adhesive layer.

[0020] Preferably, in step (3), after the degradation layer is provided on the surface layer, the adhesive material is coated.

[0021] The present invention has the following beneficial effects: The present invention provides a new self-adhesive sticker, the degradation rate of the adhesive layer material is high, and the disintegration rate reaches more than 90% within 180 days under composting conditions. In addition, the present invention also provides a self-adhesive sticker with a controllable degree of degradation. When the self-adhesive sticker needs to be torn off, the degradation liquid inside the self-adhesive sticker can be manually released to help the self-adhesive sticker disintegrate and degrade from the inside. In addition, the internal degradation liquid can be selected from a microbial preparation that is adapted to the local environment, thereby not only achieving accelerated degradation of the self-adhesive sticker, but also achieving more effects such as improving the soil quality and environment of the location where the self-adhesive sticker is discarded. In addition, the provision of the internal degradation liquid of the self-adhesive sticker will form special textures and shapes on the surface of the self-adhesive sticker. Based on this feature, users can customize self-adhesive stickers with different textures to display brands or other required patterns and shapes, which has great commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A side sectional view of the self-adhesive sticker provided by the present invention;

[0023] Figure 2 for Figure 1 A magnified image of point A;

[0024] Figure 3 This is a top view of the self-adhesive sticker provided by the present invention (including the perspective structure of the storage bin and storage channel). DETAILED DESCRIPTION

[0025] The present invention provides a degradable self-adhesive sticker. The self-adhesive sticker is composed of a surface layer 10, an adhesive layer 20 and a bottom layer 30, and the surface layer 10, the adhesive layer 20 and the bottom layer 30 are all made of degradable materials. An optional scheme is that the adhesive layer 20 is a starch-based material, and the optional formula is, for example, by weight, including 10 to 30 parts of starch, 10 to 20 parts of polycaprolactone (PCL), 0.5 to 10 parts of alkali, 0.3 to 1 part of ZnO, 0.3 to 1 part of diisopropylbenzene peroxide (DCP), and 50 to 150 parts of water. The alkali is any one of NaOH and Ca(OH)2, preferably NaOH. The adhesive layer is coated on the surface layer, and the bottom layer is a degradable release paper, which is a mature prior art.

[0026] A preferred solution is: a degradation layer is provided between the surface layer 10 and the adhesive layer 20 to help the surface layer 10 and the adhesive layer 20 to degrade. The degradation layer stores a substance that can accelerate the degradation of the surface layer 10 and the adhesive layer 20. A more preferred solution is: the substance that can accelerate the degradation stored in the degradation layer will be released when the self-adhesive sticker is torn off the adhered object or when needed. It should be noted that the adhesive layer material can also be selected from other existing degradable related materials.

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. The data obtained are all average values ​​obtained after at least 3 repetitions, and all the data obtained in each repetition are valid data.

[0028] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0029] Example

[0030] 1. Preparation of three-layer adhesive and demonstration of degradation performance

[0031] (1) Commercially available self-adhesive surface material (purchased from Dongguan Jinzhen Packaging Material Co., Ltd.) and bottom layer material (glassine paper coated with silicone oil). Prepare the adhesive material by the following method: at 62°C, weigh 15 parts of starch by weight, add it to 80 parts of water, stir while adding, and after fully mixing, slowly add 1 part of NaOH while maintaining stirring. After the addition is complete and the mixture is fully mixed, keep stirring and add 10 parts of PCL. After the addition is complete and the mixture is fully mixed, keep stirring and add 0.5 parts of ZnO and 0.5 parts of DCP. After all the materials have been added, continue stirring for 2 hours until all the components are fully mixed and present a uniform flowing liquid state, and naturally cool to room temperature to obtain the adhesive material.

[0032] The surface layer material and the bottom layer material are cut into required sizes and shapes to obtain the surface layer 10 and the bottom layer 30 respectively. The adhesive material is coated on the surface layer 10 and dried at 120°C to form the adhesive layer 20. The coating amount of the adhesive material on the surface layer material is 2×10 -3 g / cm 2 The bottom layer 30 is applied to the side of the adhesive layer 20 that is not in contact with the surface layer 10 to obtain the desired self-adhesive label.

[0033] (2) Cut the sticker into 10cm pieces 2 The square blocks were tested for 180 days according to the disintegration rate test method under household composting conditions in GBT 41010-2021 "Degradability and Labeling Requirements for Biodegradable Plastics and Products". After 180 days, the self-adhesive sample was obviously broken, with a disintegration rate of 91%.

[0034] 2. Preparation and degradation performance demonstration of four-layer structure adhesive

[0035] (1) Prepare the three-layer self-adhesive adhesive by the method of step 1 to obtain the surface layer material, the adhesive layer material and the bottom layer material. Figures 1 to 3 As shown, the storage bin 41 is prepared by enclosing a surface layer material or other degradable materials. The storage bin 41 can be as follows Figure 1 The storage bin 41 is in a cubic shape, and may also be in other shapes such as a sphere, an ellipsoid, etc. The storage bin 41 stores powder materials that can accelerate the degradation of the surface layer 10 and the adhesive layer 20 in a liquid state.

[0036] In one embodiment, microbial powder, such as microbial freeze-dried powder, is stored in the storage bin 41. The microbial powder is selected from microorganisms that can accelerate the degradation of the surface layer and the adhesive layer and are pollution-free to the environment. Microorganisms that adapt to the local environment can also be selected according to the usage scenario of the self-adhesive sticker and the environment in which it may be discarded. For example, if the adhesive layer selects the starch-based formula of this embodiment, and the self-adhesive sticker may be discarded in the field, the microorganism can select Bacillus amyloliquefaciens, which can accelerate the degradation of the self-adhesive sticker on the one hand, and on the other hand, it can also play a certain role in soil improvement and improving the quality of agricultural products. In this embodiment, Bacillus amyloliquefaciens freeze-dried powder purchased from Shandong Jingbao Biotechnology Co., Ltd. (which can be stored at room temperature for more than 12 months) is placed in the storage bin 41.

[0037] The storage bin 41 is placed between the surface layer 10 and the adhesive layer 20. A sharp opening groove 43 is provided at one end of the storage bin 41, and the opening groove 43 is connected to the inside of the storage bin 41. The sharp end of the opening groove 43 is located inside the storage channel 42. The material of the storage channel 42 can also be selected from the surface layer material or other degradable materials. The storage channel 42 is divided into two independent spaces where liquids do not circulate by a partition membrane 44, one of which accommodates the opening groove 43, and there is a certain distance between the opening groove 43 and the partition membrane 44; the other space stores a dissolving liquid, which corresponds to the powder material stored in the storage bin 41, and can quickly dissolve the powder material after contacting the powder material. In this embodiment, the dissolving liquid in the storage channel 42 is a freeze-dried dissolving resuscitation liquid of Bacillus amyloliquefaciens freeze-dried powder (which can be stored at room temperature for more than 12 months).

[0038] When the storage bin 41 is squeezed and deformed by external force, the opening groove 43 moves toward the separation membrane 44, puncturing the separation membrane 44, and the dissolving liquid in the storage channel 42 enters the storage bin 41 along the opening groove 43 to dissolve the powder material. Keeping the squeezed and deformed state, the liquid that has dissolved the powder material will quickly flow throughout the storage channel 42, accelerating the degradation of the storage channel 42. After the storage channel 42 is degraded, it will further penetrate and accelerate the degradation of the surface layer 10 and the adhesive layer 20.

[0039] When not deformed by extrusion, the opening groove 43 is in a dry state for a long time, maintaining a certain hardness, and can quickly puncture the separation membrane 44. In practice, in order to facilitate better puncturing of the separation membrane 44, the opening groove 43 can also be prepared using a harder plastic material alone.

[0040] The storage channel 42 can be configured in various shapes as required and can be widely distributed between the surface layer 10 and the adhesive layer 20. Except for the separation membrane 44 separating the space for accommodating the opening groove 43, the internal space of the storage channel 42 is completely connected and stores the dissolved liquid. Figure 3 The dotted line in the figure is an arrangement of the storage bin 41 and the storage channel 42 which are not visible from a normal viewing angle in the top view of the sticker. The denser and more evenly the storage channels 42 are arranged between the surface layer 10 and the adhesive layer 20, the better the degradation effect. In addition, after the storage channel 42 and the internal dissolving liquid are set, the surface of the sticker can be seen with faint lines formed by the storage channel 42, and a special feel is formed. When in use, the storage channel 42 can be designed into the shape of a corporate trademark, or other special patterns, and then combined with coloring, etc., to present a special design effect of the appearance of the sticker, achieving multiple goals at one stroke.

[0041] The preferred solution is to make a special symbol or mark on the surface layer 10 corresponding to the storage bin 41. When the sticker needs to be torn off or the degradation needs to be accelerated, the special symbol or mark is squeezed for a few seconds (if the sticker is shaken back and forth during squeezing, the effect is better), and the opening groove 43 can pierce the separation membrane 44, and the liquid that has dissolved the powder material will flow throughout the storage channel 42.

[0042] In order to avoid accidental squeezing during transportation or use, a more preferred solution is: a protective shell 12 is set on the surface layer 10 corresponding to the storage bin 41. The material of the protective shell 12 can be selected as a degradable plastic with a certain hardness, such as thickened PLC plastic. A certain depression is set on the surface layer 10 below the protective shell 12. When the degradation of the adhesive needs to be accelerated, the protective shell 12 can be crushed with a hard object such as a fingernail.

[0043] The surface layer 10 of some self-adhesive stickers has many designs and shapes, and is relatively thick. Direct extrusion may not ensure that the opening groove 43 can puncture the separation membrane 44. Therefore, a more preferred solution is: an extrusion rod 11 is set in the surface layer 10 corresponding to the upper part of the storage bin 41. Under normal conditions, the extrusion rod 11 is separated from the storage bin 41 with a certain distance. When accelerated degradation is required, the corresponding position of the surface layer 10 is extruded, and the extrusion rod 11 moves toward the storage bin 41 accordingly, extruding the storage bin 41 to deform, thereby driving the opening groove 43 to move toward the separation membrane 44 and puncture the separation membrane 44.

[0044] In this embodiment, the surface layer material and the bottom layer material are cut into 50cm 2The surface layer 10 and the bottom layer 30 are obtained respectively. The storage bin 41 and the storage channel 42 are prepared by using the surface layer material. Figure 3 In the arrangement mode, grooves for storing the storage bins 41 and storage channels 42 are processed on the side of the surface layer 10 facing the adhesive layer 20, and a thin layer of adhesive material is applied (not shown in the figure). Then the storage bins 41 and storage channels 42 are quickly placed in the corresponding positions. Then the adhesive material is applied to the remaining positions of the surface layer 10, the bottom of the storage bins 41 and storage channels 42, and the adhesive layer 20 is formed after drying at 120°C. The amount of adhesive material applied is 2×10 -3 g / cm 2 Carefully apply the bottom layer 30 to the side of the adhesive layer 20 that is not in contact with the surface layer 10 to obtain the desired self-adhesive sticker. Since the surface layer material in this embodiment is commercially available, the thickness is not thick, and the test is performed immediately after preparation, the protective shell 12 and the extrusion rod 11 are not provided.

[0045] (2) The adhesive surface layer 10 is squeezed to the position corresponding to the storage bin 41 for 5 seconds, and the adhesive is shaken back and forth while being squeezed, and then tested for 180 days according to the disintegration rate test method under household composting conditions in GBT 41010-2021 "Degradability and Labeling Requirements for Biodegradable Plastics and Products". After 180 days, the adhesive sample was checked and it was obviously broken, with a disintegration rate of 98%.

[0046] The embodiments described above are only descriptions of the preferred modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations, modifications, and substitutions made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A degradable adhesive label, characterized in that: The self-adhesive adhesive comprises a surface layer (10), an adhesive layer (20) and a bottom layer (30), wherein the adhesive layer (20) is a starch-based material, and the formula comprises, by weight: 10 to 30 parts of starch, 10 to 20 parts of polycaprolactone, 0.5 to 10 parts of alkali, 0.3 to 1 part of ZnO, 0.3 to 1 part of diisopropylbenzene peroxide, and 50 to 150 parts of water; A degradation layer is provided between the surface layer (10) and the adhesive layer (20); a substance capable of accelerating the degradation of the surface layer (10) and the adhesive layer (20) is stored in the degradation layer, the degradation layer comprises a storage bin (41), a dry powder material is stored in the storage bin (41), and the dry powder material can accelerate the degradation of the surface layer (10) and the adhesive layer (20) when in a liquid state; a protective shell (12) is provided at a position of the surface layer (10) corresponding to the storage bin (41); The storage bin (41) is placed between the surface layer (10) and the adhesive layer (20), close to the storage channel (42), and the storage channel (42) contains a dissolving liquid that can dissolve the powder material in the storage bin (41); the storage bin (41) can be connected to the storage channel (42) when it is necessary to accelerate the degradation of the adhesive. A sharp opening groove (43) is provided at one end of the storage bin (41), and the opening groove (43) is communicated with the interior of the storage bin (41); the sharp end of the opening groove (43) is located inside the storage channel (42); The storage channel (42) is divided into two independent spaces where liquids do not flow into each other by a separation membrane (44), one of which accommodates the open groove (43), and there is a certain distance between the open groove (43) and the separation membrane (44); the other space stores the dissolved liquid.

2. The degradable adhesive label according to claim 1, characterized in that: The base is any one of NaOH and Ca(OH)2.

3. The degradable adhesive label according to claim 1, characterized in that: In terms of weight, the adhesive layer (20) has a formula of: 15 parts of starch, 80 parts of water, 1 part of NaOH, 10 parts of polycaprolactone, 0.5 parts of ZnO and 0.5 parts of diisopropylbenzene peroxide.

4. The degradable adhesive label according to claim 1, characterized in that: The release time of the substances stored in the degradation layer is controllable.

5. The method for preparing the degradable adhesive according to any one of claims 1 to 4, characterized in that: The steps include: (1) Weigh starch by weight and add it to water, stirring while adding. After fully mixing, slowly add NaOH while keeping stirring. After adding and fully mixing, keep stirring and add PCL. After adding and fully mixing, keep stirring and add ZnO and DCP. After all materials are added, continue to stir until all components are fully mixed and present a uniform flowing liquid state, and naturally cool to room temperature to obtain an adhesive material. (2) cutting the surface layer material and the bottom layer material into required sizes and shapes to obtain the surface layer (10) and the bottom layer (30), respectively; (3) applying an adhesive material onto the surface layer (10) and forming an adhesive layer (20) after drying; (4) Laying the bottom layer (30) on the side of the adhesive layer (20) that is not in contact with the surface layer (10) to obtain the desired self-adhesive layer.

6. The preparation method according to claim 5, characterized in that: In step (3), after the degradation layer is provided on the surface layer (10), the adhesive material is coated.

Citation Information

Patent Citations

  • Biodegradable adhesive sticker label

    CN102867459A

  • PET adhesive label

    CN206451449U